My own private Idaho [videorecording (DVD)] - Van Sant, Gus; Phoenix, River; Reeves, Keanu; Russo, James; Richert, William, 1942-; Harvey, Rodney, 1967-1998 (Criterion collection, 2005)
Mike, a sensitive narcoleptic who dreams of the mother who abandoned him, and Scott, the rebellious son of a prominent family and the object of Mike's desire, embark on a quest from the grungy streets of Portland to the open highways of the Pacific Northwest, in search of an elusive place called home.